Rancangan Bangun Sistem Informasi Monitoring Perjanjian Kerjasama Berbasis Website dengan Integrasi Firebase - Siti Maria Ulfa; Firman Santoso; Nur Azize (Department of Science and Technology Ibrahimy University, 2024)
Information systems have become core in managing business activities. Cooperation agreements, as an essential element in organizations, require efficient management to ensure the continuity of successful cooperation. Although there are already information systems in use, there are still challenges related to coordination, evaluation, and tracking of cooperation agreements. Therefore, this research aims to integrate Firebase technology into the cooperation agreement monitoring information system. By utilizing Firebase features such as Authentication, real-time database, and hosting, this system will also be connected to notifications via email and WhatsApp API to provide information about the status of the agreement submission. The development of this system uses the waterfall method and UML diagrams. The diagrams used are use case diagrams, activity, and class diagrams. Actors involved in this system are partners, admins, visitors, and office heads. Implementing the system developed using Firebase integration facilitates the process of submitting, monitoring, and evaluating cooperation and application development.